Transforming Anti-Radicalism Education through Synergized Curriculum, Social Engagement, and Adaptive Learning Strategies - Rini Werdiningsih; Tri Lestari Hadiati; Wahyu Wirasati; Adellya Naswa Maristy; Shofiyatun Nisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Radicalism is an ideology or view that is very extreme and tends to oppose the values ​​of Pancasila and threatens the integrity of the Republic of Indonesia. The development of radicalism and terrorism needs to be prevented early on in the family environment, schools/universities, and the community environment. This study aims to determine the effect of socially adaptive learning, curriculum management, and social networking models on anti-radicalism characters among students, using a quantitative approach. The object of research is Junior High Schools (SMP) in Central Java. The sampling method uses a purposive technique. The results of the study show that Through rigorous path analysis, this study reveals the significant role of effective curriculum management, social networks, and socially adaptive learning in forming resistance to radical ideology. These findings have substantial theoretical and practical implications, but also raise critical questions that need to be explored further.